Offside: The Misunderstanding in Restricting Jemaat Ahmadiyah Indonesia's Right to Freedom of Religion - Ahmad, Ansar; Ramadhani, Tasya Nur (Global Legal Review, 2022)
Jemaat Ahmadiyah Indonesia ("JAI") in Sintang became the victim of an intolerant action by several members of the Muslim Alliance, which attacked and destroyed the Miftahul Huda mosque belonging to the JAI that resulted in the destruction of the mosque and the burning of a building behind it. The root of the problem, turns out, is not anchored in intolerant actions by certain religious groups, instead it lies in government policies that tend to restrict JAI's right to freedom of religion. However, the restriction on the right to freedom of religion in Sintang is only the tip of the iceberg of the restrictions on JAI's religious freedom rights by the JAI’s Joint Decree. This paper discusses the role of the state in limiting the right to freedom of religion based on various human rights instruments and principles. It further determines the suitability of restrictions on freedom of religion in the JAI’s Joint Decree from a human rights perspective. This paper finds that the right to freedom of religion is a non-derogable right, but, it can be restricted under article 18 paragraph (3) of the ICCPR, which can only be applied on its manifestations that are necessary to protect public safety, order, health, or morals, as well as the basic rights and freedoms of others. Nevertheless, the restriction must be directly related to the specific need and should not be imposed or applied in a discriminatory manner or non-discriminative. Besides that, this paper finds that the restrictions in JAI’s Joint Decree are in violation of the ICCPR and the principles of the right to freedom of religion because of two things, namely the forum internum’s intervention and misunderstanding of forum externum’s restriction. First, the government has intervened JAI’s forum internum by determining that JAI’s interpretation deviates from Islamic teachings, which is prohibited due to any reason. Second, the government has erroneously imposed forum externum’s restriction by prohibiting JAI to spread its interpretation, which is also prohibited because the JAI’s forum externum has no direct relation with the disturbance of public safety, order, health, morals or the fundamental rights and freedoms of others.